NEEDS ANALYSIS OF LOCAL WISDOM-BASED DIGITAL LEARNING MEDIA WITH A SCIENTIFIC APPROACH - Damayanti, Astried; Hartiningsari, Dwi Putri; Setiawan, Angga (Edukasi: Jurnal Pendidikan, 2025)
This study aims to determine the needs analysis of students of digital learning media that uses local wisdom and scientific approach. This needs analysis is purposed at learning English. The research subjects were 8th grade students from 5 private junior high schools in Trenggalek with total of 108 respondents. The research method was descriptive quantitative with questionnaire as the main instrument. While observation and documentation were used as supporting data. The result showed that students needed interesting digital media which was easy to access and could be used anytime and anywhere. The result also indicated that the scientific approach had been implemented by the teacher. The students had interest in recognizing culture or tradition of local wisdom and scientific approach. It can be concluded that it is necessary to develop interesting learning digital media which was easy to access through website by applying local wisdom and scientific approaches.